Virtual reality filmaking: Analysis of Queerskins: A love story, an approach to volumetric cinema. (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
Currently, virtual reality technology offers to the audiovisual industry new ways of telling stories. One of the techniques that enables video image recording and its implementation in 3D virtual environments is volumetric capture, which raises an approach between conventional cinema methods and those of fictional audiovisual discourses for VR. In this context, we carry out a previous bibliographical review, to address the study of the applicability of traditional production techniques to virtual reality productions. Subsequently, we designed an analysis model for this type of work, based on the concepts of Heeter (1992), Slater and Wilbur (1997), which is based on the effect of presence as a basis for the immersion of the spectator in the diegetic universe of the VR artworks. The exposed results are obtained after analyzing Queerskins: a love story (Szilak and Tsiboulsk, 2018), one of the first virtual reality short films with volumetric filmmaking.
Keywords: Volumetric cinema; virtual reality; interactivity; filmmaking; VR cinematography